MEMPERKUAT EKSISTENSI PENDIDIKAN BAHASA DAN SASTRA INDONESIA DI ERA REVOLUSI INDUSTRI 4.0 - Haryani, Neni (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This paper seeks to encourage the need for massive reform in the body of Indonesian Literature education. This reform is needed so that literary education is able to answer the challenges and demands of the times that continue to change. In addition, this paper also seeks to provide solutions to language and literary education (especially the learning of Indonesian literature) in the face of the Era of Industrial Revolution 4.0. As dikertahui together, that era 4.0 has a broad impact on all lines of life, including in the field of education. The era that gave birth to this disruption phenomenon requires the world of language and literary education to participate in adjusting themselves. So it is necessary to update and innovate the system, governance, curriculum, human resource competencies, facilities and infrastructure, culture, work ethic, and others. Otherwise, literary education will be increasingly left behind and obsolete. Therefore, it is necessary to look for concrete steps for Islamic education in order to be able to remain competitive in this disruption era. The solution step is to participate in discussing themselves.